How many sarees and tunics it takes to “make” an Indian? - Iorio, Patrícia de Miranda (2010)
The purpose of this article is to analyze the representation of Indians on India: a Love Story, a Gloria Perez’s soap opera. It starts with the confrontation of the coding and deconding work of Indian costume language with a recoding process that adjusted it to the Brazilian code and TV aesthetics. It also compares the “reading” and the “translation” accomplished by the soap opera costume designer with the final results from the exhibited scenes. Taken as a language, the costume about the Other on this TV fiction reveals itself far from the stereotype and carnavalization. The study still shows that the original work done in India: a Love Story inaugurates a new category of costume on the manual of costume productions for TV.